1959
DOI: 10.1002/aic.690050124
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the thermal decomposition of calcium carbonate

Abstract: IReaction time the time duri *In run 42 the'aphere waa m#e by turning down a cylinder, and it waa later found that the thermocouple junction was at.0.37 of the diameter inafead of 0.50. &In run 43 O.OlO-in.-diameter wire was used, but two 1-in. sections on eaoh aide of the junction were flattened to a cross section of 0.003 in. X 0.026 in. 'In run 45 four strands of 0.001-in.Tdiam. wire were uaed fof mechanical atrength. ' In runs 40, 43, 48, and 49 the calcium, oxide was ao extepsively cracked that density fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

1959
1959
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 13 publications
1
37
0
Order By: Relevance
“…The absence of a defined crystalline structure indicates that the calcite had been calcined and recarbonated (Gourdin and Kingery, 1975;Kingery et al, 1988). During the calcination process there is a large volume change which leads to large cracks in the surface layer of calcium carbonate, causing it to decompose into small particles (Satterfield and Feakes, 1959). These observations confirm the presence of lime.…”
Section: Characterisation Of the White Substancesmentioning
confidence: 76%
“…The absence of a defined crystalline structure indicates that the calcite had been calcined and recarbonated (Gourdin and Kingery, 1975;Kingery et al, 1988). During the calcination process there is a large volume change which leads to large cracks in the surface layer of calcium carbonate, causing it to decompose into small particles (Satterfield and Feakes, 1959). These observations confirm the presence of lime.…”
Section: Characterisation Of the White Substancesmentioning
confidence: 76%
“…According to the mechanisms for individual reactions suggested by previous investigators [1][2][3][7][8][9]12] and the present observations of XRD, it is proper at this stage to summarize the reation steps involved in the present system. [6] [2] [7] [8] [3] The standard free energy changes for these reaction steps are listed in Table II for reference.…”
Section: A Analysis By Xrdmentioning
confidence: 88%
“…Figure 5 shows scanning electron micrographs of spent catalyst, carbon black, and calcium carbonate. Figure 5(a) reveals that the grain of the spent catalyst is of irregular shape with size about 100 ϫ 10 Ϫ6 m. Carbon grains shown in Figure 5(b) are very fine and are about 1.0 ϫ 10 Ϫ6 m in C (s) ϩ CO 2 (g) ϭ 2CO (g) [7,8] CaO (s) ϩ COS (g) ϭ CaS (s) ϩ CO 2 (g) [7,8] ZnS (s) ϩ CO (g) ϭ Zn (g) ϩ COS (g) [7,8] ZnO (s) ϩ CO (g) ϭ Zn (g) ϩ CO 2 (g) [1] CaCO 3 (s) ϭ CaO (s) ϩ CO 2 (g) [12] size. The grains are capable of aggregating easily to form a large agglomerate with size ranging from 10 ϫ 10 Ϫ6 to 80 ϫ 10 Ϫ6 m. The grain of calcium carbonate, shown in Figure 5(c), also agglomerates easily and the approximate size of the grain is 1.0 ϫ 10 Ϫ6 m while the aggregate size of it cannot be observed from SEM picture.…”
Section: A Analysis By Xrdmentioning
confidence: 99%
See 1 more Smart Citation
“…McKewan [8], Satterfield and Feaks [9], Ingraham and Marier [10], Shen and Smith [11], Narsimhan [12], Koloberdin et al [13], Rubiera et al [7], Ruckensteiner et al [14] and Khinast et al [6] have reported that the rate is controlled by heat transfer and chemical reaction at the interface. Borgwardt [5] reported on calcination kinetics and surface area of dispersed limestone particles.…”
Section: Introductionmentioning
confidence: 99%